Arquitecturas de software sin servidor : un caso de estudio para el despliegue en amazon Web Services, Microsoft azure e IBM Bluemix (2017)
"The present graduation project intends to identify peculiarities in computation services provided by Amazon Web Services, Microsoft Azure and IBM Bluemix used to build software applications without managing servers. To this purpose, three applications were developed, one for each company mentioned above, with the same functional and quality requirements. Each application with their respective development process were analyzed in terms of: response time, development ease, testing ease, resource monitoring and financial investment. It is expected that such information will be useful to software developers and architects, so that they can infer advantages and disadvantages in their own projects using serverless computing. -- Tomado del Formato de Documento de Grado.